Leveraging audiovisual speech perception to measure anticipatory coarticulation - Redford, Melissa A. (J Acoust Soc Am, 2018)
A noninvasive method for accurately measuring anticipatory coarticulation at experimentally defined temporal locations is introduced. The method leverages work in audiovisual (AV) speech perception to provide a synthetic and robust measure that can be used to inform psycholinguistic theory. In this validation study, speakers were audio-video recorded while producing simple subject-verb-object sentences with contrasting object noun rhymes. Coarticulatory resistance of target noun onsets was manipulated as was metrical context for the determiner that modified the noun. Individual sentences were then gated from the verb to sentence end at segmental landmarks. These stimuli were presented to perceivers who were tasked with guessing the sentence-final rhyme. An audio-only condition was included to estimate the contribution of visual information to perceivers' performance. Findings were that perceivers accurately identified rhymes earlier in the AV condition than in the audio-only condition (i.e., at determiner onset vs determiner vowel). Effects of coarticulatory resistance and metrical context were similar across conditions and consistent with previous work on coarticulation. These findings were further validated with acoustic measurement of the determiner vowel and a cumulative video-based measure of perioral movement. Overall, gated AV speech perception can be used to test specific hypotheses regarding coarticulatory scope and strength in running speech.